Temporal trends in step test performance for Chinese adults between 2000 and 2014 - Yang Liu; Mark S. Tremblay; Grant R. Tomkinson (Elsevier, 2021)
Backgroud/Objective: Cardiorespiratory endurance is an excellent marker of functional endurance and health among adults. The aim of this study was to estimate temporal trends in step test performance for Chinese adults between 2000 and 2014. Methods: Apparently healthy adults aged 20-59 years were included. Nationally representative step test data (n = 603,977) from 2000, 2005, 2010, and 2014 were reported descriptively by the China Physical Fitness Surveillance Center. Temporal trends in means were estimated at the sex-age level for all adults and separate location/occupation groups using sample-weighted linear regression, with trends in distributional characteristics described visually and estimated as the ratio of coefficients of variation (CVs). Results: Collectively, there was a negligible improvement in mean step test performance of 0.12 standardized effect sizes (95% confidence interval (95%CI): 0.11-0.13). Negligible to small improvements were observed for all age, sex, location, and occupation groups. Variability declined substantially over time (ratio of CVs (95%CI): 0.86 (0.86-0.86)), with negligible to large improvements in those below the 10th percentile, and negligible to moderate declines in those above the 90th percentile. Conclusion: There have been negligible to large improvements in step test performance for low to average performing Chinese adults since 2000, which may be meaningful to public health because low endurance is an important risk factor for all-cause mortality.